Problem-solving Ability of Fifth-graders in Mathematical Word Problem - ., Rosmayasari; Suryadi, Didi; Herman, Tatang; Prabawanto, Sufiyani Prabawanto (KnE Social Sciences, 2024)
This study aims to analyze the students’ problem-solving skills in solving the daily problems that deal with the operations of fractions. This research was conducted at a State Elementary School in Bandung City, West Java Province, Indonesia. The research method used was a qualitative approach with a narrative case study method. The participants in this study were 36 students of grade V. Data were collected from student test results, interviews, results between students and teachers. Data analysis was performed using interpretational analysis. The results show that the fifth-grade still have difficulty in understanding the problems. Other interesting findings were: (1) Some students still do not understand the rules or how to change mixed numbers into ordinary fractions or vice versa. (2) Some students still do not understand how to design and implement solving strategies. (3) Some students still do not understand the concepts and procedures of counting operations, such as addition, subtraction, multiplication, and division. (4) Some students do not conclude the final result from the answer to the story problem (5). Some students do not validate the question of the story problem, she/he just give answers to mathematical solutions. Keywords: problem-solving ability, mathematical word